0264 The Effects of Previous Night's Sleep, 12-Hour Shift, and Workload on Sleepiness in Emergency Medical Service Providers. (27th May 2020) - Pavuluri, H; Schmidt, W M; Amalean, A; Fowler, L
Abstract: Introduction: Shift-work has been shown to be detrimental to workers in many ways, including having negative effects on sleep. Many factors related to shift-work can contribute to these negative effects, including increased workload and less sleep the previous night. The effects of shift-work on sleep have been studied extensively in nurses and physicians, but this research is lacking in paramedics and emergency medical technicians (EMTs). This study assessed the effects of previous night's sleep, day- versus night-shift, and workload on sleepiness in paramedics and EMTs. Methods: Thirty-three EMTs and paramedics were tested before and after their 12-hour (either day- or night-) shift. Testing consisted of questions about previous night's sleep, pupillometry to assess pupillary response for physiological sleepiness, and the Stanford Sleepiness Scale for subjective sleepiness. The number of calls made per shift was used to quantify workload/call volume. Results: An analysis of variance assessed the effect of shift (day/night), previous night's sleep, and workload on post-shift sleepiness. Pupillometry demonstrated that participants were sleepier after 12-hour shifts, but those who slept 8–9 hours the night before were less affected. Pupillary response indicated higher levels of sleepiness following the night-shift compared to the day-shift. This was contrary to perceived sleepiness, which was higher after the day-shift than the night-shift. Higher call volume resulted in a sleepier physiological response, and this effect was shown to be dependent upon the shift. Conclusion: Performing shift-work results in increased sleepiness in workers, especially after a night shift. However, physiological sleepiness does not always correspond to perceived sleepiness. In addition, increased workload results in increased sleepiness, especially during the day shift. This highlights the importance of obtaining 8–9 hours of sleep before a 12-hour shift to protect against the effects of sleepiness on patient care and EMS workers themselves. Support: This was funded in part by a UofSC Provost Grant.